Psychological and Psychopharmacological Interventions in Psychocardiology - Kahl, Kai G.; Stapel, Britta; Correll, Christoph U. (Frontiers in Psychiatry, 2022)
Patients with severe mental disorders have an increased risk to develop cardiovascular diseases, and cardiovascular diseases are frequently comorbid with especially adjustment disorder, anxiety and depressive disorders. Therefore, physicians need to be aware of treatment strategies relating to comorbid patients, and key concerns related to the prescriptions of psychopharmacological drugs. Cognitive behavioral therapy and treatment strategies that belong to the third wave of cognitive-behavioral therapy are well established psychological treatments for patients comorbid with cardiovascular disease and mental disorders. Internet-based psychological treatments may also be considered. In more severe cases, psychopharmacological drugs are frequently used. Although well tolerated and efficacious in general, drug- and dose-dependent side effects have to be considered. Among antidepressants selective serotonin reuptake inhibitors (SSRIs), selective serotonin and noradrenalin reuptake inhibitors (SNRIs), and newer antidepressants such as mirtazapine, bupropion, agomelatine and vortioxetine can be considered, while tricyclic agents (TCAs) should be avoided due to their cardiac side effects. Mood stabilizers have been associated with arrhythmias, and some typical and atypical antipsychotic drugs are described to increase the risk of QTc prolongation and metabolic side effects, although differences exist between the different drugs. Benzodiazepines are generally considered safe in cardiovascular diseases when administered for a short time period, and may mitigate symptoms of acute coronary syndrome. Laboratory and ECG monitoring is always recommended in psychopharmacological drug treated patients on a regular basis. Presence of a heart disease should not preclude patients from necessary treatment interventions, but may require a careful risk-benefit evaluation.